Fundamental solution of the steady oscillations equations in couple stress micropolar viscoelastic thermoelastic solid - Sahrawat, Ravinder Kumar; Rani, Sonam (Zielona Góra: Uniwersytet Zielonogórski)
In this article, we have studied the case of steady oscillations to solve the system of differential equations by using elementary functions in the theory of microploar couple stress viscoelastic solid. Four waves were discovered: two coupled longitudinal waves and two coupled transverse waves that propagate at various wave speeds. The penetration depth, specific loss, attenuation coefficients, and phase velocity-all of which have been computed numerically and plotted graphically for the LS and GL models-are affected by couple stresses and viscous parameters. Specific cases are created and contrasted with the earlier outcomes.
Keywords: fundamental solution; plane waves; steady oscillations; couple stress; viscoelastic; micropolar; thermoelastic